PERAN PETUGAS PENGENDALI ORGANISME PENGGANGGU TUMBUHAN DALAM MENERAPKAN KONSEP PENGENDALIAN HAMA TERPADU ( Studi Kasus pada Dinas Pertanian dan Kehutanan Kabupaten Kulon Progo, Provinsi Daerah Istimewa Yogyakarta) - , KURNIATI DWI ASTUTI; , Prof. Dr. Warsito Utomo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Plant pest control has an important role in improving agricultural production. One effort to control pests and diseases of plants with plant control methods known to the system Integrated Pest Management ( IPM ). Integrated Pest Management is a method of combining a variety of control techniques in a plan. Such efforts need to be supported by the existence of an agricultural institution that should serve as a kind of consultancy that is always ready to serve the difficulties experienced by the farmers in terms of crop pest control. So the government established the existence of functional officials controlling plant pests. In the context of decentralization, local government of Kulon Progo Regency also formed Functional officials controlling plant pests of Kulon Progo Regency. This study aims to determine the role of the functional officials controlling plant pests in carrying out its duties and functions to empower farmers in applying the concept of Integrated Pest Management, as well as to identify factors that influence the effectiveness of the role functional officials controlling plant pests. The method used is descriptive qualitative. Data was collected by interview, observation and documentation analysis. The results of this study indicate that the role of functional officials controlling plant pests in implementing the concept of IPM still not effective. There are several factors that lead to the ineffectiveness of the role of functional officials controlling plant pests in performing their duties. These factors were seen in four characteristics. Organizational characteristics that influence is the least number of existing officers. Environmental characteristics that influence is inequality in the process of transformation of IPM knowledge to farmers, lack of awareness to implement IPM by farmers, lack of support from other parties, and the type of officer that workers centric. Worker characteristics that influence is lack of motivation to work and the weak of organization ties, and uneven capacity of officers. Characteristics management policies and practices that influence is vertical communication is less well established, the lack of personnel role in the activities, and supporting infrastructure facilities is not all fulfilled. And to improve the effectiveness of the role of the functional officials controlling plant pests, advice given, among others, the recruitment officer will need to be adjusted to the needs of qualified personnel in Crop Protection, made the public space enough for officers to be able to actualize themselves in community-related activities, synergies among institutions engaged in agriculture with a fair division of roles, and increase the facilitation of the officers.